1999
DOI: 10.7326/0003-4819-130-7-199904060-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary ω-3 Fatty Acids on Coronary Atherosclerosis

Abstract: Dietary intake of omega-3 fatty acids modestly mitigates the course of coronary atherosclerosis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(79 citation statements)
references
References 31 publications
1
74
0
4
Order By: Relevance
“…Regular consumption of fish oil supplements appears to reduce the risk of coronary artery disease in some observational studies (Saldeen et al 2002;von Schacky et al 1999) but not others (Sacks et al 1995). Recent randomized controlled trials have shown that LCPUFA in fish oil or fish can play a role in secondary prevention of coronary heart disease (Harper and Jacobson, 2005;Kris-Etherton et al, 2002).…”
Section: Cardiovascular Outcomes-althoughmentioning
confidence: 99%
“…Regular consumption of fish oil supplements appears to reduce the risk of coronary artery disease in some observational studies (Saldeen et al 2002;von Schacky et al 1999) but not others (Sacks et al 1995). Recent randomized controlled trials have shown that LCPUFA in fish oil or fish can play a role in secondary prevention of coronary heart disease (Harper and Jacobson, 2005;Kris-Etherton et al, 2002).…”
Section: Cardiovascular Outcomes-althoughmentioning
confidence: 99%
“…Consumption of these molecules has been associated with a lipid-lowering effect in vivo (30) and reductions in heart disease (31,32). Two specific ⍀-3 fatty acids, eicosapentaenoic acid (EPA, 20:5) and docosahexaenoic acid (DHA, 22:6), have been shown to stimulate the degradation of newly synthesized apoB by cultured rat hepatocytes and hepatoma (McArdle RH-7777; McA) cells (29,33).…”
mentioning
confidence: 99%
“…Epidemiologic studies suggest that 1-2 fish meals per week or as little as 30-35 g/d of fish throughout life decrease the risk of coronary heart disease relative to those who do not eat any fish 22,33) . Furthermore, in the study by von Schacky et al, patients with coronary artery disease who ingested approximately 1.5 g of omega-3 fatty acids per day for 2 years had less progression and more regression of coronary artery disease on coronary angiography than did comparable patients who ingested a placebo 71) . For the secondary prevention of coronary heart disease, 300 g of fatty fish providing 2.5 gms EPA from fish or fish oil/wk decreased the risk of sudden death by 29% 31) .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%